Genetic and Phylogenetic Characteristics of Pasteurella multocida Isolates From Different Host Species - Peng, Zhong; Liang, Wan; Wang, Fei; Xu, Zhuofei; Xie, Zhihao; Lian, Zhenghan; Hua, Lin; Zhou, Rui; Chen, Huanchun; Wu, Bin (Frontiers in Microbiology, 2018)
Pasteurella multocida is a leading cause of respiratory diseases in many host species. To understand the genetic characteristics of P. multocida strains isolated from different host species, we sequenced the genomic DNA of P. multocida isolated from pigs and analyzed the genetic characteristics of strains from avian species, bovine species, pigs and rabbits using whole genome sequence (WGS) data. Our results found that a capsular: lipopolysaccharide (LPS): multilocus sequence typing (MLST) genotype A: L1: ST129 (43.75%) was predominant in avian P. multocida; while genotypes B: L2: ST122 (60.00%) and A: L3: ST79 (30.00%) were predominate in bovine P. multocida; genotype D: L6: ST50 (37.50%) in porcine P. multocida; and genotype A: L3: ST9 (76.47%) in rabbit P. multocida. Comparative genomic analysis of P. multocida from different host species found that there are no genes in the P. multocida genome that are specific to any type of host. Phylogenetic analysis using either whole-genome single nucleotide polymorphisms (SNPs) or the set of SNPs present in all single-copy core genes across genomes showed that P. multocida strains with the same LPS genotype and MLST genotype were clustered together, suggesting the combining both the LPS and MLST typing schemes better explained the topology seen in the P. multocida phylogeny.